Bacterial survival in radiopharmaceutical solutions: a critical impact on current practices - Julien Leenhardt; Luc Choisnard; Maelle Plasse; Valérie Ardisson; Nicolas de Leiris; Loic Djaileb; Pierrick Bedouch; Marie-Dominique Brunet (SpringerOpen, 2023)
Abstract Background The aim of this brief communication is to highlight the potential bacteriological risk linked to the processes control of radiopharmaceutical preparations made in a radiopharmacy laboratory. Survival rate of Pseudomonas aeruginosa (ATCC: 27853) or Staphylococcus aureus (ATCC: 25923) or Staphylococcus epidermidis (ATCC: 1228) in multidose technetium-99 m solution was studied. Results Depending on the nature and level of contamination by pathogenic bacteria, the lethal effect of radioactivity is not systematically observed. We found that P. aeruginosa was indeed affected by radioactivity. However, this was not the case for S. epidermidis, as the quantity of bacteria found in both solutions (radioactive and non-radioactive) was rapidly reduced, probably due to a lack of nutrients. Finally, the example of S. aureus is an intermediate case where we observed that high radioactivity affected the bacteria, as did the absence of nutrients in the reaction medium. The results were discussed in the light of current practices on the sterility test method, which recommends waiting for radioactivity to decay before carrying out the sterility test. Conclusion In terms of patient safety, the results run counter to current practice and the latest EANM recommendation of 2021 that radiopharmaceutical preparations should be decayed before sterility testing.